The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/ijfe.1913
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of risk management tools: Financial hedging, corporate diversification and liquidity

Abstract: What kind of firm benefits more from financial hedging, the focused or diversified? In fact, the benefit of financial hedging depends on diversification policies. By analyzing the interaction between financial hedging and corporate diversification in a theoretical model for a financially constrained firm, we find that focused firms have relatively higher marginal value of hedging in general static environment. However, dynamic analysis results show that an important synergy between financial hedging and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
(108 reference statements)
1
5
0
Order By: Relevance
“…This paper aligns closely with Wong (2007), Gamba and Triantis (2014), and Jiang and Feng (2020) who focused on integrated risk management. However, they fail to differentiate between internal flexibility and hedging instruments.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…This paper aligns closely with Wong (2007), Gamba and Triantis (2014), and Jiang and Feng (2020) who focused on integrated risk management. However, they fail to differentiate between internal flexibility and hedging instruments.…”
Section: Introductionsupporting
confidence: 69%
“…Wong (2007) investigated financial and operational hedging in a static environment. Gamba and Triantis (2014) and Jiang and Feng (2020) assumed fixed capital. We incorporated intertemporal liquidity and capital decisions because internal flexibility is important for risk management (Disatnik et al, 2014;Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the research of Kiambati (2020) and Sathyamoorthi et al (2020) demonstrated that there is a relationship between risk management and profitability or shareholder market value among the commercial banks. Furthermore, Jiang and Feng (2020) emphasize the importance of risk management capabilities which is hardly observable but contributes much to firm value. Thus, our third hypothesis is worth considering:H2 Risk management positively influences the bank's performance .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The advantages and features of the expert approach to risk assessment [28,36] and mathematical methods to identify and assess risks are the most often discussed topics in the literature [37][38][39][40]. The development of mathematical tools that allows one to form an optimal trajectory for managing several risks simultaneously is given in [41].…”
Section: Literature Reviewmentioning
confidence: 99%